160 years of Australian telecommunications - Gerrand, Peter (Journal of Telecommunications and the Digital Economy, 2014)
The Australian telecommunications industry has reached its 160th anniversary this year measured from the completion of its first electrical telegraph network on 3 March 1854, linking Melbourne to Williamstown. The back story to the implementation of that first network suggests that Lieutenant Governor Charles La Trobe and the colony’s first General-Superintendent of Telegraphy, Samuel McGowan, should be celebrated as the founders of Australian telecommunications: the visionary and his appointee, the entrepreneurial project manager. A brief overview is given of how the Australian telecommunications industry has evolved to the present day, including the evolution of the Telecommunications Society of Australia (now TelSoc), a society of volunteers supporting the industry since 1874, i.e. for 140 years of the industry’s 160 years.